Does Islamic Attributes Matters? Empirical Study on Halal Tourism in Surakarta - Nisa, Ulin; Indah Piliyanti (Jurnal Ilmiah Ekonomi Islam, 2025)
Surakarta has a very diverse tourist potential. As a Muslim-majority country, Islamic attributes are thought to be influential in increasing tourist visits. Therefore, this study aims to explain how Islamic attributes, quality of service, destination image and tourist loyalty influence tourism in Surakarta. The type of research used is quantitative research with a random sample of 200 respondents from a population using simple random sampling techniques. The data collection was carried out using questionnaires that were distributed directly at some tourist points in Surakarta. Data analyzed using the Smart Partial Least Square model. In addition, Islamic attributes directly influence the image of tourist destinations in Surakarta with a t-statistic of 4,586 and a p-value of 0,000. The quality of service from tourism has a direct influence on the picture of the tourist destination in the city of Surakarta, with a statistic of 7,278 and p- value of 0.000. Furthermore, the Islamic Attribute directly influences the loyalty of tourists who have visited it with the statistic t-values of 4,072 and 0,000, and the quality of the service directly affects tourist loyalty so that tourists want to make a return visit with the t-static value of 3,236 and the p- value of 0.001. The Islamic destination attribute frequently seen and heard by the public in connection with tourism in Surakarta directly influenced tourists' loyalty with statistical values of 3,567 and p - value of 0,000. This study successfully proved that destination image variables, Islamic attributes, quality of service, and loyalty of tourists play an important role in halal tourism of the city of Surakarta as well as tourists who will visit or tourists that will make repeated visits.